Meningkatkan Pengalaman Pengguna Melalui Perancangan UI/UX Website Company Profile “Ben Dadi Apik” dengan Pendekatan Design Thinking - Firmansyah, Firdaus; Hibatullah, Muhammad Raflie; Avorizano, Arry (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2025)
The advancement of digital technology drives construction service companies such as “Ben Dadi Apik” to establish a professional and informative online presence. A company profile website serves as a primary medium to build credibility and reach potential clients. This study aims to enhance user experience (UX) by designing the user interface (UI) of the “Ben Dadi Apik” website using the Design Thinking approach. The methodology includes empathizing, defining, ideating, prototyping, and testing stages, with an emphasis on user persona development and evaluation using the System Usability Scale (SUS). The results indicate that the implemented UI/UX design successfully delivers an intuitive and informative user experience, significantly improving the company's professional image. This approach ensures the website functions as an effective and user-centric digital communication platform.